Determining accounting students' design thinking skills: The role of artificial intelligence usage and digital literacy - Darmawan, Rahmat; Widiastuti, Harjanti (Journal of Accounting and Investment, 2025)
Research aims: This study aims to examine the influence of Artificial Intelligence (AI) usage and digital literacy on the design thinking skills of accounting students, as well as examine the role of digital literacy as a mediating variable in the relationship between AI usage and design thinking skills.Design/Methodology/Approach: A quantitative approach was used through a survey of 323 accounting students from various universities in Indonesia. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the direct and indirect influences between variables.Research findings show that AI usage and digital literacy directly and positively influence design thinking skills. Furthermore, digital literacy mediates the positive influence of AI usage on design thinking skills. Variations in relationships were also found based on the type of institution and the student's semester level.Theoretical contribution/Originality: This study expands the application of Social Cognitive Theory (SCT) by placing digital literacy as a personal factor that mediates the influence of technology on complex thinking skills. These findings also emphasize the importance of considering institutional context and learning experiences in using accounting education technology.Practitioner/Policy implication: The study's results confirm the importance of a learning strategy focusing on AI integration and strengthening digital literacy to support the development of 21st-century skills.Research limitation/Implication: Variations in institutional readiness and access to technology become external factors that cannot be controlled. Future research needs to include learning experiences and institutional environment as contextual variables.